Small-Scale Deep Network for DCT-Based Images Classification - Borhanuddin B.; Jamil N.; Chen S.D.; Baharuddin M.Z.; Tan K.S.Z.; Ooi T.W.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Convolutional neural networks; Deep neural networks; Digital storage; Discrete cosine transforms; Image classification; Image coding; Object recognition; Compressed images; Data redundancy; Discrete Cosine Transform(DCT); Images classification; Information reduction; Neural network model; Raw image data; Research trends; Image compression